2018
DOI: 10.4314/ahs.v18i2.17
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanics of lower limb injuries in frontal-impact road traffic collisions

Abstract: AimWe aimed to review the biomechanics of lower limb injuries caused by frontal-impact road traffic collisions.MethodsIn this narrative review, we identified articles through pubmed, Scopus and Science Direct search engines for the period of 1990–2014. Search terms included: “biomechanics”, “lower limb injury”, “hip injury”, “knee injury”, “foot and ankle injury” and “frontal impact collision”. We studied factors affecting the anatomical site, frequency and severity of the injuries.ResultsThe most common repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…It is well established that women have, on average, shorter statures than their male counterparts (Duyar and Pelin, 2003) and so, based on the findings here, are at a higher risk of leg injury. This corroborates with road-traffic frontal collision research (Dischinger et al, 1995;Crandall et al, 1996;Welsh et al, 2003;Austin 2012, Ammori andAbu-Zidan, 2018); Austin (2012) reported 4-7 times higher odds for female drivers to present a leg fracture, and Dischinger et al (1995) reported a 20% risk of lower limb fractures for females compared to 13% for male drivers with most injuries sustained at the foot and ankle; they also report that, when grouped by stature, the smaller statures were at a higher risk of leg injury than taller statures. Of course, there are biological and anatomical differences between genders other than stature that may contribute to differences in the risk of lower leg injury.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is well established that women have, on average, shorter statures than their male counterparts (Duyar and Pelin, 2003) and so, based on the findings here, are at a higher risk of leg injury. This corroborates with road-traffic frontal collision research (Dischinger et al, 1995;Crandall et al, 1996;Welsh et al, 2003;Austin 2012, Ammori andAbu-Zidan, 2018); Austin (2012) reported 4-7 times higher odds for female drivers to present a leg fracture, and Dischinger et al (1995) reported a 20% risk of lower limb fractures for females compared to 13% for male drivers with most injuries sustained at the foot and ankle; they also report that, when grouped by stature, the smaller statures were at a higher risk of leg injury than taller statures. Of course, there are biological and anatomical differences between genders other than stature that may contribute to differences in the risk of lower leg injury.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, whilst in the civilian automotive setting it is known that stature and gender may affect the severity of leg injury (Crandall et al, 1996;Welsh et al, 2003;Malczyk et al, 2013;Hu et al, 2017;Ammori and Abu-Zidan, 2018), there have been no such studies for UBB. Stature can vary substantially amongst vehicle occupants; the height of 180 American soldiers was found to vary between 1.53 and 1.76 m for women and 1.52 and 1.93 m for men (Darter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…49 This would cause the lower extremities to be trapped under the dashboard in a more stationary manner, while the rest of the trunk and extremities are free to recoil from the collision. 48 Additionally, current restraint systems and airbags do not protect the legs in collisions. 21 The ratio of mass between the body and the head may serve to explain the increased risk of neck injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The work by Jibrin and others11 highlights the histo-pathological pattern of brain tumours in Nigeria. The rest of the NCD papers, deal with diagnosis of ischemic disease12, rheumatoid arthritis13, the retina14, hearing loss15, limb injury16, poisoning17, and glaucoma 18…”
Section: Non Communicable Diseasesmentioning
confidence: 99%